Modeling the potential impact of administering vaccines against Clostridioides difficile infection to individuals in healthcare facilities. Issue 37 (18th August 2020) - Toth, Damon J.A.; Keegan, Lindsay T.; Samore, Matthew H.; Khader, Karim; O'Hagan, Justin J.; Yu, Holly; Quintana, Alvaro; Swerdlow, David L.
Abstract: Background: A vaccine against Clostridioides difficile infection (CDI) is in development. While the vaccine has potential to both directly protect those vaccinated and mitigate transmission by reducing environmental contamination, the impact of the vaccine on C. difficile colonization remains unclear. Consequently, the transmission-reduction effect of the vaccine depends on the contribution of symptomatic CDI to overall transmission of C. difficile . Methods: We designed a simulation model of CDI among patients in a network of 10 hospitals and nursing homes and calibrated the model using estimates of transmissibility from whole genome sequencing studies that estimated the fraction of CDI attributable to transmission from other CDI patients. We assumed the vaccine reduced the rate of progression to CDI among carriers by 25–95% after completion of a 3-dose vaccine course administered to randomly chosen patients at facility discharge. We simulated the administration of this vaccination campaign and tallied effects over 5 years. Results: We estimated 30 times higher infectivity of CDI patients compared to other carriers. Simulations of the vaccination campaign produced an average reduction of 3–16 CDI cases per 1000 vaccinated patients, with 2–11 of those cases prevented among those vaccinated and 1–5 prevented among unvaccinated patients. Conclusions: Our findings demonstrate potential for a vaccine against CDI to reduce transmissions in healthcare facilities, even with no direct effect on carriage susceptibility. The vaccine's population impact will increase if received by individuals at risk for CDI onset in high-transmission settings.